An item analysis of the achievement test in biology and the processes of science test used in five regional science teaching centers in the 1972 Science Summer Institute - Esmundo, Rosalinda M. Ramirez 1941- ([Quezon City publisher not identified], 1974)
The implementation of the Processes of Science Test and Achievement Test in Biology undertaken by the Science Education Center (SEC) of the University of the Philippines in the 1972 Science Summer Institue Program was evaluated in this study. Specifically, the study sought: (1) to analyze achievement through item analysis of two tests given to teacher participants of the summer institute in Biology, and (2) to assess the effectiveness of the Science Summer Institute in terms of a marked increase in cognitive skills among the participants.
Thesis (Master of Arts in Teaching)--University of the Philippines.
Keywords: Biology -- Examinations